Strain Localization and Shear Band Propagation in Ductile Materials - Bordignon, Nicola; Piccolroaz, Andrea; Dal Corso, Francesco; Bigoni, Davide (Frontiers in Materials, 2015)
A model of a shear band as a zero-thickness nonlinear interface is proposed and tested using finite element simulations. An imperfection approach is used in this model where a shear band, that is assumed to lie in a ductile matrix material (obeying von Mises plasticity with linear hardening), is present from the beginning of loading and is considered to be a zone in which yielding occurs before the rest of the matrix. This approach is contrasted with a perturbative approach, developed for a J2-deformation theory material, in which the shear band is modelled to emerge at a certain stage of a uniform deformation. Both approaches concur in showing that the shear bands (differently from cracks) propagate rectilinearly under shear loading and that a strong stress concentration should be expected to be present at the tip of the shear band, two key features in the understanding of failure mechanisms of ductile materials.